The family Cretapsychidae (Insecta, Trichoptera) from mid-Cretaceous Burmese amber, with descriptions of two new species - Wichard, Wilfried; Espeland, Marianne (European Journal of Taxonomy, 2022)
The Cretaceous family Cretapsychidae Wichard, 2021 belongs to the superfamily Sericostomatoidea Stephens, 1836 and is characterized by the five-segmented maxillary palps, with the second segment being the longest and the following three segments becoming successively smaller, and the tibial spur formula 2/2/4. In addition, the wing venation is characterized by apical forks II, III, and V in the forewings and forks I, III, and V in the hindwings. The two newly described species (C. kachini sp. nov. and C. myanmari sp. nov.) extend the genus Cretapsyche Wichard, Neumann, Müller & Wang, 2018 to six extinct species, all of which were found in mid-Cretaceous Burmese amber from Kachin State, Myanmar.